Inconsistent Patterns of Soil Fauna Biodiversity and Soil Physicochemical Characteristic Along an Urbanization Gradient - Yu, Shiqin; Wu, Zhifeng; Xu, Guoliang; Li, Cheng; Wu, Zhijian; Li, Zengguang; Chen, Xiaohua; Lin, Miaojun; Fang, Xueru; Lin, Yongquan (Frontiers in Ecology and Evolution, 2022)
Urbanization has induced substantial changes in soil physicochemical characteristic, which plays an important role in regulating soil fauna biodiversity in forests and grasslands. However, less is known about the urbanization effect on soil fauna biodiversity and how soil physicochemical changes mediate this effect. Along an urbanization gradient in the city of Guangzhou, we established four sites with different urbanization intensities, including an urban site, two suburban sites, and a rural site, and then studied their soil physicochemical characteristic and soil fauna biodiversity. The soil physicochemical characteristic dramatically changed along the urbanization gradient. In contrast, the soil fauna biodiversity exhibited a very different pattern. Soil fauna abundance was highest in the suburban sites. Moreover, there were significant changes of Pielou’s evenness and community structure in the suburban sites. Soil fauna biodiversity property in the urban site was similar to that in the rural site, except that the rural site was characterized by Enchytraeidae while the urban site was not characterized by any taxa. Our linear and canonical correspondence analysis models suggested that soil physicochemical characteristic only contributed a little to the variance of soil fauna abundance (19%), taxa number (27%), and community structure (12%). In contrast, soil physicochemical characteristic explained about half of the variance in Shannon’s diversity and Pielou’s evenness. However, with urbanization intensity increasing, soil physicochemical changes could both increase and decrease the diversity and evenness. Thus, our results revealed an inconsistent pattern between soil fauna biodiversity and soil physicochemical characteristic along an urbanization gradient. This study suggested that soil physicochemical change was less important as expected in regulating soil fauna biodiversity pattern under an urbanization context. To elucidate the effect of urbanization on soil fauna biodiversity, further studies should take other urbanization agents into account.